Impersonate affecting users' attitude toward facebook in Egypt - Hassan El Hoby, Hany Mohamed; Zeki, Akram M. (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Social networking sites such as Facebook have mushroomed very rapidly. Anyone with an email address can make an account as long as he accepts the terms and conditions of the website regarding privacy. There are several pages of celebrities, public figures and famous personalities being tricked by hackers on the Web. The real problem arises when a subscriber follows the wrong page taking it as real. This study has been done to share the opinions from Facebook account holders. It intends to impart awareness regarding the phenomenon "Impersonation" on Facebook, which means the imposter sending a bad message from another account which made as a real account. This study has been conducted to assess the impersonation on Facebook in the Egyptian context. This study prove, impersonate has a negative impact in the Egyptian society from a sample of 210 respondents by quantitative research. The study shows people has a higher education level, is greater than awareness about the existence of impersonation.